PERSPEKTIF MUAMALAH ISLAM TERHADAP JUAL BELI IKAN NELAYAN DENGAN TENGKULAK DI DESA KUALA CANGKOI, LAPANG, ACEH UTARA - Yoesrizal M Yoesoef (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2017)
Along with the economic system development in Kuala Cangkoi Village, Lapang subdistrict of North Aceh Regency, there have been many transaction forms. One of the hot trending selling and buying practices in today’s society is selling and buying using contract system that only benefits one party, namely the middlemen who lend the capital to the fishermen. In this case, fishermen only can sell the fish to those middlemen where the fish price will be in hand of middlemen personal determination only. This research aims to explain the perspective of Islamic economic law toward transaction issue between fishermen and middlemen in Kuala Cangkoi, Lapang, North Aceh Regency. The result of this study indicates that the practice between fishermen and the middlemen for fish trading is inappropriate with the legal terms of Islamic economic law viewpoint. This is due to the above condition where the fishermen have been restrained to sell the caught fish to all wholesalers they want because they are burdened by loan capital gotten from a specific middlemen. This case is proved by numerous disputes occurred between fishermen and middlemen which is triggered by the unacceptable activity where the fishermen sell their fish to the other middlemen while the loan capital they get from the previous middleman has not been fully paid off. Whereas, in the concept of Islamic economic law, the transfer of wealth, in this case, the sale and purchase should be done by the mutual willingness and without being based on any coercion whatsoever. Keyword: Sale and Purchase, Fisherman, Middleman, Islamic Economic Law